Self-Perceived Mental Health Status, Digital Activity, and Physical Distancing in the Context of Lockdown Versus Not-in-Lockdown Measures in Italy and Croatia: Cross-Sectional Study in the Early Ascending Phase of the COVID-19 Pandemic in March 2020 - Kopilaš, Vanja; Hasratian, Anni M.; Martinelli, Lucia; Ivkić, Goran; Brajković, Lovorka; Gajović, Srećko (Frontiers in Psychology, 2021)
The novelty of the COVID-19 pandemic is that it occurs in the globalized society enhanced by digital capabilities. Our aim was to analyze the psychological and emotional states of participants in different pandemic-related contexts including their digital and physical distancing behaviors. The online survey was applied during the ascending phase of the pandemic in March 2020 in two neighboring EU countries, Italy and Croatia. The study subjects involved four groups, two directly affected by epidemiological measures and two serving as controls – (1) participants from Italy who were in lockdown (Italy group), (2) participants from Croatia who were not in lockdown, but who were in direct contact with an infected person and underwent epidemiological measures (CRO-contact group), (3) participants from Croatia who were in analogous situation but not near the same infected person (CRO-no contact group) and (4) participants from Croatia who were not aware of any infected person (CRO-unrelated group). The survey consisted of validated scales of psychological and emotional states, and custom-made questionnaires on digital (online) and physical (off-line) behavior of the participants. Italy group in lockdown had higher self-perceived scores for depression, stress, post-traumatic intrusion and avoidance, as well as highest digital activity and physical distancing than the not-in-lockdown Croatian groups. The insight in extent of online activities and off-line isolation allowed introducing Digital Activity and Physical Distancing Scores. Self-perceived post-traumatic avoidance was higher in both the Italy and CRO-contact groups than the control CRO-no contact and CRO-unrelated groups, and higher avoidance correlated with higher Digital Activity and Physical Distancing Scores. Being in direct contact with the infected person the CRO-contact group had no other alterations than unexpectedly lower post-traumatic hyperarousal when compared to the Italy group. The Italy group in lockdown demonstrated higher self-perceived psychological toll together with higher digital activity and physical distancing than Croatian groups not in lockdown, even when compared to the affected CRO-contact group. The study outcomes suggest that the general emergency measures influenced citizens in lockdown more than an exposure to the virus through direct contact with an infected person.